2017
DOI: 10.1039/c6sc03859j
|View full text |Cite
|
Sign up to set email alerts
|

AIEgen-based theranostic system: targeted imaging of cancer cells and adjuvant amplification of antitumor efficacy of paclitaxel

Abstract: An AIEgen-based theranostic system is developed to amplify the antitumor efficacy of paclitaxel with a synergistic effect of “0 + 1 > 1”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 50 publications
0
69
0
Order By: Relevance
“…[ 58 ] Interestingly, most AIE photosensitizers are activated by visible or ultraviolet (UV) irradiation. [ 59 ] NIR is converted into visible or UV light by UCNPs. Since NIR irradiation can penetrate tissues to higher depths, these UCNPs can be used as noninvasive PDT agents.…”
Section: Strategies For Targeting the Tmementioning
confidence: 99%
“…[ 58 ] Interestingly, most AIE photosensitizers are activated by visible or ultraviolet (UV) irradiation. [ 59 ] NIR is converted into visible or UV light by UCNPs. Since NIR irradiation can penetrate tissues to higher depths, these UCNPs can be used as noninvasive PDT agents.…”
Section: Strategies For Targeting the Tmementioning
confidence: 99%
“…Aiming to enhance the therapeutic efficiency of drugs, adjuvants have been widely employed in CHT. Tang and Ding's groups 123 reported for the first time an AIE-active adjuvant named TPE-Py-FFGYSA, which was composed of a TPE fragment, FFG tripeptide and a peptide sequence YSAYPDSVPMMS (YSA) ( Figure 25 ). The FFG unit does not only play a role as a linker between TPE and YSA, but is also capable of promoting the AIE performance of TPE-Py-FFGYSA as well, resulting from more efficient restriction of intramolecular motions (RIM) thanks to the existence of an aromatic capping group in FFG.…”
Section: Recent Developmentmentioning
confidence: 99%
“…This work suggests a new research direction that a photosensitizer can serve as a nontoxic adjuvant to amplify the antitumor efficacy of radiotherapy. The same groups also demonstrated that using AIE adjuvant as a photosensitizer can amplify the antitumor efficacy of paclitaxel with an IC 50 value of 7.8 × 10 −9 m , which is only 10.3% of that of paclitaxel alone …”
Section: Cellular Imaging and Theranosticsmentioning
confidence: 94%